Ethos e identidade no discurso religioso fundador: uma abordagem semiótica do corpus paulinum - Machado, Domingos de Sousa (2022)
Based on the theoretical-methodological assumptions of Discursive Semiotics, this thesis aims to investigate how the ethos of the enunciation actor of the founder biblical discourse is constructed in the epistolary text of the paulinum corpus. In order to attain this general scope, we also specifically aim to: a) analyze the discursive strategies used by the enunciator in the construction of meanings in the Pauline epistolary discourse in view of the make-believe; b) verify the recurrence of the enunciator's ways of saying that refer to a specific way of being in the world, an end-image, an identity effect of the enunciation actor; c) establish the relationship between the construction of the ethos and the presence of one or several enunciating ethical identities in the Pauline epistolary; and d) to contribute in a transversal way to the discussions around the authorship of this Pauline acquis. The paulinum corpus is traditionally composed of thirteen letters. However, taking into account the principle that, according to Discini (2015), supported by Brøndal (1948, 1986), the whole is in the parts, since there is a structure that systematizes and schematizes a way of saying as an identity effect , as a voice, a body and a character, we cut out of this discursive totality, only six, two as representative of each one of the three groups in which the epistles are classified: a) of the Proto-Paulines or authentic, Galatians and Philemon; 2) of the Deutero-Pauline or doubtful ones, Ephesians and 2 Thessalonians; and 3) of the pseudo-Pauline or non-authentic ones, 2 Timothy and Titus. The theoretical-methodological framework is built in dialogue with authors such as Greimas (1974, 1975, 1976, 1979, 2014, 2002), Greimas and Courtés (1985, 2016), Fontanille (2008), Greimas and Fontanille (1993), Fontanille and Zilberberg (2001), Zilberberg (2004, 2006a, 2006b, 2007, 2011, 2012), Barros (1990, 1995, 2002, 2007) and Bertrand (2003). The category of ethos, transposed from Aristotelian Rhetoric and duly incorporated by Semiotics, is assumed here according to the works of Fiorin (1995, 2004, 2007, 2008a, 2008b, 2016), Saraiva (2011, 2012, 2017), and Discini (2003, 2005, 2006, 2007, 2010, 2013, 2015, and 2016), in close dialogue with the texts of Maingueneau (1984, 1997, 2000, 2008, 2011, 2016, 2020). Based on the levels of narrative, discursive and tensive structures, the analyzes made reveal the presence in the corpus of a set of recurrent ethical traits, associated with the authoritative and submissive ethé of an apostle; to a convinced and uncompromising theologian or preacher; to the mildness, humility, and benevolence of a pastor or fatherly leader; and with the affectionate, condescending, and fraternal ethos of a father or a generous spiritual guide. We identified an oscillation in the way in which each of these traits are present in epistolary assertions, sometimes accentuated, sometimes toned, therefore, can be identified in terms of degrees of presence. Despite the different ethé of the narrators, the presence and convergence of these identity traits allow us to infer a corporal héxis – a way of thinking, speaking, feeling and interpreting the things of the world. Whoever was the effective author or authors of these texts, the important thing is that, the figurative enunciator in these texts by the actor Paulo, when enunciating, recurrently, builds these images of himself from specific scenography, to persuade and gain the adhesion of its recipients to its discursive project.